Pemanfaatan Sains Dan Teknologi Dalam Pengukuran Arah Kiblat Di Indonesia - Muthmainnah Muthmainnah; Fattah Setiawan Santoso (Universitas Cokroaminoto Yogyakarta, 2020)
The direction of the Qibla is very important in salat prayer. Having to know the direction means being part of a series of prerequisite prayer requirements. For the people of Mecca and those who live there, Qibla is not a problem because they do not experience difficulties in determining it. However, for countries and cities outside Mecca in the State of Saudi Arabia it is a very important issue as to which direction the Qibla to the Ka'bah is right to accurate. There are several methods that have been invented and have been practiced and achieved accurate results, but not all ulama of fiqh can fully accept them. Through the study of Indonesian literature on the direction of the Qibla and discussed with descriptive qualitative, opinions and reasons are further explored that help address the need for discussion in astronomy. Not all circles are capable of accepting technological developments, there are some groups who refuse that it is sufficient to determine the direction of the Qibla facing west. Among the groups who reject it, namely traditional scholars or ancient kyai, they believe that the mosque built by the wali cannot be wrong or may not face the Qibla.